If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 60 = 2x + 124 Reorder the terms: 60 + 6x = 2x + 124 Reorder the terms: 60 + 6x = 124 + 2x Solving 60 + 6x = 124 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 60 + 6x + -2x = 124 + 2x + -2x Combine like terms: 6x + -2x = 4x 60 + 4x = 124 + 2x + -2x Combine like terms: 2x + -2x = 0 60 + 4x = 124 + 0 60 + 4x = 124 Add '-60' to each side of the equation. 60 + -60 + 4x = 124 + -60 Combine like terms: 60 + -60 = 0 0 + 4x = 124 + -60 4x = 124 + -60 Combine like terms: 124 + -60 = 64 4x = 64 Divide each side by '4'. x = 16 Simplifying x = 16
| 3x-18=8x+9 | | 4(6x-7)+2= | | m-11=10 | | x^3+xy^3-6y^3=0 | | -2y-6=8 | | 5a-2a+a=8-16 | | 3x-6+7x=6-2 | | 5x+4x+3x=8-12 | | 2132=x^2+11x | | 4x^3-56x^2+192x=0 | | x+9-6=2-11 | | 7-9=a-5 | | 2(5a+1)-9a=4-3 | | 9x-18=10x-12 | | 5=7+0.6k | | x+4=136 | | 3(j+5)=5(11-f) | | f+4=6g | | 2y-3=3 | | s=-4+6t | | -21-3= | | 2800=1200+0.08s | | s=-3+6t-1 | | 3x+(x-6)=180 | | 5z-7z=-4 | | 0.5zx^2+vs+Y=0 | | 0.5gt^2+vt+x=0solvet | | -2-x+5-5x= | | 0.5gt^2+vt+x=0 | | 64a-72b= | | y^2-w^2=0 | | 9m^2n^2-12mn+4=0 |